2011
DOI: 10.1177/0021998311398382
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic crash model for energy absorption in braided composite materials. Part I: Viscoplastic material model

Abstract: A dynamic crash model is developed and implemented to model the failure behavior and energy absorption of braided composite structures. Part I describes the development and theoretical foundation of a viscoplastic material model that captures the rate-dependent behavior present in braided composite materials. Part II presents the implementation of the model into a FEM program and contains experimental results for tubes crushed from quasi-static rate to 4000 mm/s rates used to verify the model. The model is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It is important to note that those models attend to fully find out the parameters that primarily affect the impact energy absorption of a composite material. Flesher et al (2011) implemented a material model with viscoplastic constitutive behavior and other significant material phenomena to simulate the crash performance of braided composite tubes. And they concluded that the variation of tube structure, braid geometry, and matrix strength in the model will affect the specific energy absorption of braided composite cubes.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that those models attend to fully find out the parameters that primarily affect the impact energy absorption of a composite material. Flesher et al (2011) implemented a material model with viscoplastic constitutive behavior and other significant material phenomena to simulate the crash performance of braided composite tubes. And they concluded that the variation of tube structure, braid geometry, and matrix strength in the model will affect the specific energy absorption of braided composite cubes.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters, namely, the strength of different directions, were obtained from earlier studies by the SACL members. 3032 Table 2 summarizes the material properties as the input parameters for the material model.
Figure 4.Carbon fiber composite facesheet tensile experiment results.
…”
Section: Model Development and Calibrationmentioning
confidence: 99%
“…To model the thermal-mechanical coupled constitutive behavior of 3-D braided composite manufactured by carbon fiber and epoxy resin under transverse impact compression loading at different temperatures, a temperature-dependent and rate-dependent material model is developed from the works [20][21][22][23][24].…”
Section: Thermal-mechanical Coupled Constitutive Materials Modelingmentioning
confidence: 99%